Change To A State Islamic University In Indonesia And The Quality Of Education Services - Ahmad Qurtubi (Journal of Educational Administration, 2018)
Modernization Islamic Higher can make these adjustments, it will create a new college paradigm. UIN from IAIN and IAIN from STAIN are useless unless changed. True UIN development philosophy is not simply to build an independent worker, but also to develop scientific identity. UIN's science and technology don't castrate Islamic studies programs or its identity. UIN, as a college-based Islamic science, must establish a strong science. Integrate S1, S2, and S3 into majors and courses. Globalization of education policy execution should modify UIN's academic climate to establish Islam's science. Pride in the college motto UIN as a pioneer and excel in the field of Islamic is more than "political jargon," however; it requires a shift in perspective, appreciation, and habit in order to fully harness and leverage the potential of the UIN's most precious wealth: the budhi-sense and morality of all people in the community independent of the UIN with capital itself. A concrete commitment is one that is backed up by a fair and equitable distribution of the organization's profits. For UIN managers, adopting a new way of thinking, appreciating and discarding conventional management practices, and putting these ideas into action through internal and external collaborative agreements, all while having the guts to compete with external organizations and foster internal competition, is an act of political courage. A competitive edge can be gained through risk-taking.